Lin28A/CENPE Promoting the Proliferation and Chemoresistance of Acute Myeloid Leukemia - Shi, Mingyue; Niu, Junwei; Niu, Xiaona; Guo, Honggang; Bai, Yanliang; Shi, Jie; Li, Weiya; Sun, Kai; Chen, Yuqing; Shao, Fengmin (Frontiers in Oncology, 2021)
The prognosis of chemoresistant acute myeloid leukemia (AML) is still poor, mainly owing to the sustained proliferation ability of leukemic cells, while the microtubules have a major role in sustaining the continuity of cell cycle. In the present study, we have identified CENPE, a microtubular kinesin-like motor protein that is highly expressed in the peripheral blood of patients with chemoresistant AML. In our in vitro studies, knockdown of CENPE expression resulted in the suppression of proliferation of myeloid leukemia cells and reversal of cytarabine (Ara-C) chemoresistance. Furthermore, Lin28A, one of the RNA-binding oncogene proteins that increase cell proliferation and invasion and contribute to unfavorable treatment responses in certain malignancies, was found to be remarkably correlated with CENPE expression in chemoresistance AML. Overexpression of LIN28A promoted the proliferation and Ara-C chemoresistance of leukemic cells. RIP assay, RNA pull-down, and dual luciferase reporter analyses indicated that LIN28A bound specifically to the promoter region GGAGA of CENPE. In addition, the impacts of LIN28A on cell growth, apoptosis, cell cycle progression, and Ara-C chemoresistance were reverted by the knockdown of CENPE. Hence, Lin28A/CENPE has enhanced the proliferation and chemoresistance of AML, and therefore, it could be a prospective candidate for AML treatment.